Rebusan Buah Asam dan Jahe Sebagai Upaya Mengurangi Dismenore - Trio Gustin (Faletehan Health Journal, 2019)
Every healthy woman will get experience a menstruation cycle every month. More than 50% of women in each country experience dysmenorrhea. One way to deal with dysmenorrhea is by using decoction. The purpose of this study was to determine the differences of the tamarind decoction and ginger decoction in reducing on dysmenorrhea. The design of this study was quasi experiment pre and post test with a sample of 30 students which was divided into two groups. Each group was given extract water of tamarind and ginger decoction in the morning and evening during menstruation first day to third day. Respondents were assessed for pain before and after intervention. Data was analyzed by using independent T-Test. The results of the study showed that respondents who were given tamarind decoction before intervention 60% experienced moderate pain and after the intervention 87% experienced mild pain, while respondents who were given ginger decoction before intervention 67% experienced moderate pain and after intervention 73% experienced mild pain. This study concluded that ginger decoction was more effective than tamarind decoction. It is recommended that future researchers conduct research to reduce dysmenorrhea with another herbal besides tamarind decoction or ginger decoction.